The role of teaching processes in turnover intentions, risk of burnout, and stress during COVID-19: a case study among Finnish University teacher educators - Virtanen, Päivi; Parpala, Anna (Frontiers in Education, 2023)
Previous research in teaching contexts other than Higher Education (HE) has shown that teachers struggle with stress, burnout and intention to leave the profession. There is rather scarce evidence that HE teachers’ wellbeing is affected by their teaching processes. Thus, this case study investigates how HE teacher educators’ (N=83) risk of burnout is related to their approaches to teaching, intention to leave teaching in HE and the stress experienced during COVID-19 pandemic. Based on the correlations and regression analyses, the results showed that COVID-19 pandemic had increased the work-stress of over half of the HE teacher educators, but only a few suffered from burnout and had intented to leave teaching in HE. The risk of teachers suffering from burnout was negatively related to having an interactive teaching approach, and positively related to having a transmissive teaching approach. Both intending to leave teaching and the stress experienced during COVID-19 pandemic predicted HE teacher educators’ risk of burnout. This study showed the importance of conducting more research on university teachers’ wellbeing.